A study of achievement, attitudes, teaching practices and learning environments in secondary school science laboratory classes in Papua New Guinea - Waldrip, Bruce Gordon (Curtin University, 1994)
The study combined qualitative methods (observation, interview and case study techniques) and quantitative methods (use of questionnaire and survey instruments) methods to (a) identify and describe current teaching practices in Papua New Guinea (PNG) secondary science laboratory classrooms; (b) investigate the effect of specific teaching practices on academic success on an external science achievement examinaton; and (c) investigate whether an educational productivity model for investigating factors associated with learning is applicable to a developing country context, namely, PNG. Analysis of data from 3,182 Papua New Guinea secondary students, generated revealed similar science laboratory learning environments across most high schools with Open-Endedness having the lowest score. Overall students' attitudes towards science were favourable, with boys having a more favourable attitudes than girls. Multivariate analyses showed that science academic achievement, science practical achievement and attitudes were related to quality and quantity of instruction, the science laboratory learning environment and gender. As in similar studies in other countries, male students performed significantly better than female students in external science achievement examinations. But female students achieved significantly better on a practical science process test. Finally, the study identified some specific aspects of current teaching practices in a developing country context, involving science learning environments and students' attitudes towards science.